Stromal Cell Induction of Regulatory Dendritic Cells - Owens, Benjamin M.; Kaye, Paul M. (Frontiers in Immunology, 2012)
Dendritic cells (DCs) are specialized antigen presenting cells of bone marrow origin that can exist in tissues in either an immature or mature state. DCs have a myriad of roles in immunity and tolerance induction, but are perhaps best known for their role in the activation and differentiation of naïve T cells at the onset of an acquired immune response. Over the past decade, a body of literature has developed that suggests that DCs, as well as many other myeloid cell populations, are also capable of exerting ‘regulatory’ effects on T cell responses. However, relatively little is known regarding the mechanisms by which such regulatory myeloid cells arise in vivo. In this mini-review, we first define the characteristics of ‘regulatory’ DCs (rDCs) and then focus on the contribution of non-hematopoietic stromal cells to their generation within specific tissue microenvironments. We also highlight areas of research that warrant future attention, arguing for a focusing of efforts towards a better understanding of the features of stromal cell populations that enable the induction of rDCs. Finally, we discuss how an understanding of stromal cell-myeloid cell interactions may lead to new therapeutic strategies for cancer, autoimmunity and infectious disease.